Estimating Population Abundance Of Seahorse In Sebong Bay, Bintan Island - Nugroho, Supradianto; Fadhilah, Nur; Sujatmiko, Tri Nur (Politeknik Ahli Usaha Perikanan, 2023)
The decline in seahorse populations in the wild due to high fishing activity and habitat degradation prompted the inclusion of all seahorse species in Appendix II of CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) in 2002. By being included in Appendix II of CITES, data and information on the abundance of seahorse populations become crucial as the basis for determining the quota for fishing and trade. Estimating population abundance of seahorse requires knowledge of habitat area, which can be modeled using the MaxEnt (maximum entropty). In this study, an estimation of the abundance of seahorses was carried out in the waters of Sebong Bay, Bintan Island. MaxEnt modeling was implemented with data on seahorse presence locations and environmental parameter maps consisting of chlorophyll-a as primary productivity parameter, benthic habitat as habitat type parameter, and dissolved oxygen, salinity, and pH as physiological parameters. From this model, the value of the area of suitable habitat for seahorses is 54,6 ha, while the density of seahorse in this area is 60 ind/ha, so it can be determined that the abundance of seahorses in the Sebong Bay is 3.276 individuals. Therefore, seahorse population in Sebong Bay is critically endangered since it is below the number of individuals that required to prevent the loss of quantitative genetic variation in a species.